Retrospective analysis of the efficacy and duration of botulinum toxin A injections in 30 patients with palmar hyperhidrosis. Issue 9 (19th September 2021) - Farrell, Joshua; Stewart, Thomas; Singh, Bhavneet; Singh, Gurkirat; Rosen, Robert
Abstract: Palmar hyperhidrosis is a common disorder characterised by excessive sweating due to hyperfunction of the sweat glands. It can be classified as primary disease, or secondary to other causes. It has a high morbidity, and a range of treatment options. Botulinum toxin injections inhibit the release of acetylcholine from the presynaptic receptors. It is an effective treatment; however, it is infrequently selected as only axillary hyperhidrosis currently attracts a Medicare subsidy. We conducted a retrospective review of 30 patients at a Sydney dermatology clinic who received botulinum toxin injections for palmar hyperhidrosis within the past 5 years. This study has the largest patient cohort with this condition in Australia. There was evidence for a median reduction in the Hyperhidrosis Disease Severity Scale, a qualitative self‐reported score, as well as an increasing duration of efficacy with repeated injections. There were minimal side‐effects of weakness and numbness. There is also an association between treatment of palmar disease and improvement in plantar disease, which suggests that treatment of palmar hyperhidrosis should be considered earlier and more frequently.